2019
DOI: 10.1097/mlr.0000000000001170
|View full text |Cite
|
Sign up to set email alerts
|

Individual Nurse Productivity in Preparing Patients for Discharge Is Associated With Patient Likelihood of 30-Day Return to Hospital

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…First, unmeasured confounding is an issue in all observational studies. In our prior work in acute care settings, we found that higher-productivity nurses were assigned to higher-acuity patients [24, 25, 39, 40]. Although there was no evidence of non-random nurse-patient assignments in this study and we adjusted for many patient and shift-level potential confounders, unmeasured confounding may still be present, potentially weakening statistical signals from individual nurses.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…First, unmeasured confounding is an issue in all observational studies. In our prior work in acute care settings, we found that higher-productivity nurses were assigned to higher-acuity patients [24, 25, 39, 40]. Although there was no evidence of non-random nurse-patient assignments in this study and we adjusted for many patient and shift-level potential confounders, unmeasured confounding may still be present, potentially weakening statistical signals from individual nurses.…”
Section: Discussionmentioning
confidence: 78%
“…We do not know whether there is nurse-level variability in CAABU-avoidance effectiveness. In non-ICU acute care settings, nurse-level variability in patient outcomes was recently reported for the outcomes of clinical condition improvement and patient-reported readiness for discharge [24, 25]. This area of research is important because, if clinician-level variability exists, some patients may inadvertently be receiving low quality care–even in high-performing well-staffed organizations or ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…Yashusheva and her colleagues have pioneered an approach to estimating nurse‐level variability in patient outcomes by applying an individual performance measurement method from the field of education economics, called Value‐Added Modeling (VAM) 26 . They have found evidence of significant individual nurse variability in patients’ clinical condition change during hospitalization on medical‐surgical units, 26 catheter‐associated asymptomatic bacteriuria in intensive care units, 27 and discharge preparation on medical‐surgical units 28 . Taken together, this seminal body of work has demonstrated that bedside nurses differ in their performance or “value‐added” as individual care providers to patients and that the differences among nurses have a measurable, significant effect on patient outcomes and cost of care, concluding that the data could be potentially used in performance evaluation and merit‐based payment schemes 26 …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, many parents in the current study expressed concerns about discordant family provider views of the optimal timing of hospital discharge. Disagreement about discharge readiness among physicians, nurses, and pediatric patients and families is not uncommon ( 28 30 ). Prior studies report higher rates of unplanned, hospital readmission when children and families are discharged before they feel ready to leave the hospital ( 31 ).…”
Section: Discussionmentioning
confidence: 99%